A Reflection on Global Protests over Gaza: The Role of Universities in the Public Debate (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The violent attack by Hamas on Israel on 7 October 2023, and the subsequent dramatic counteroffensive by Israeli troops in Gaza and Lebanon, have led to a growing wave of protests and counter-protests that started in the United States and then spread globally. The current wave of pro-Palestine student protests has placed universities at the centre of a complex debate that seems to have opened a “Pandora’s box” on thorny and multifaceted issues. This article aims to understand the origins, meaning, and consequences of the student movement and to explore the role of universities in the context of a major political crisis like the war in Gaza
Keywords: Social Movements; Protests; Israel; Gaza; Universities